Theory and Innovation Model of the PAI Curriculum: TEORI DAN MODEL INOVASI KURIKULUM PAI - Buhari; Obaid, Moh. Yahya; Herman; Syamsuri (RELIGI: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze innovations in the Islamic Religious Education (IRE) curriculum from the perspectives of curriculum development, competency-based learning, and character education. The study employed a qualitative approach using a library research method. Data were collected from academic books, peer-reviewed journal articles, educational policy documents, and relevant previous studies. The data were analyzed using content analysis through the stages of data reduction, data display, and conclusion drawing. The findings reveal that innovations in the IRE curriculum encompass improvements in learning objectives, instructional materials, teaching strategies, learning media, and assessment systems, all of which are oriented toward developing students’ competencies and Islamic character. The implementation of these innovations is supported by active learning approaches, including Problem-Based Learning, Project-Based Learning, collaborative learning, and the integration of digital technology to enhance instructional effectiveness. Furthermore, the curriculum incorporates Islamic values into contemporary issues such as digital literacy, religious moderation, environmental awareness, and social ethics. The successful implementation of curriculum innovation is influenced by teachers’ professional competence, institutional support, the availability of educational facilities and infrastructure, and a school culture that encourages innovation. This study concludes that innovation in the IRE curriculum is a strategic effort to develop religious, ethical, critical-thinking, and adaptive learners who are well prepared to address the challenges of twenty-first-century education